Prediction of perforation into concrete accounting for saturation ratio influence at high confinement. (October 2021) - Baroth, J.; Briffaut, M.; Vu, D.; Malecot, Y.; Daudeville, L.
Highlights: This paper provides experimental, analytical and numerical results predicting perforation of reinforced concrete slabs submitted to soft and hard impacts. Models account for free water saturation ratio and high triaxial stress Finite element simulations use a revised constitutive model for concrete (coupled damage plasticity model PRM). This paper provides analytical ballistic limit and residual velocities. These predictions depend on a deviatoric stress-based formulation of compressive strength of concrete. Abstract: This paper provides both an analytical and a finite element models aiming at better predicting possible perforation of reinforced concrete slabs submitted to impacts. Both models account for free water saturation ratio and high triaxial stress induced into concrete by the impact. Finite element simulations are performed with Abaqus explicit code using a revised constitutive model for concrete; this coupled damage plasticity model (PRM) accounts for strain rate effects and the influence of saturation ratio on the triaxial behavior. Complementary original analytical predictions of ballistic limit and residual velocities are provided for both hard and soft impacts. These predictions depend on a recent deviatoric stress-based formulation of compressive strength of concrete. Numerical and analytical results are consistent with bending and punching experimental tests.